The case for value management to be included in every construction project design process / Aini Jaapar - Jaapar, Aini (2000)
Value management (VM) in construction is the term to describe the total process of enhancing value for the Client from a project through concept to operation. While lower cost can be achieved through the traditional cost saving exercises, neither quality nor value can be guaranteed. Professionals in the industry are increasingly relying on VM to maintain the quality while keeping total cost down and at the same time attempting to optimise the value and functionality of the construction projects. The major influence in the immediate future will be a drive towards better value for money rather than lowest cost. Thus, the main target in order to ensure the factor can be achieved would be through design. This research is limited to discovering the effectiveness and benefits of value management during the design process and how value management can be best employed to benefit the Client of the construction industry. A postal survey was carried out on the Malaysian architect's exposure to value MSc in Integrated ConstructioCn OPrPojYecRt MIGanHagTem ©en Ut iTM Vltl management due to the importance of the design stage and its impact on the outcome of the construction projects. Case studies were carried out in order to give a better view on the implementation of value management study and its contribution towards the implementation of the construction project. The research showed that the Malaysian clients are slowly accepting VM as a method of achieving value and to achieve better functionality in their projects. Through the application of VM methodology during the design process stages, it was able to enhance the benefits obtained by the client and derive better value and building functionality, without necessarily increasing cost. Yet, value management still has a long journey to travel in order to be an accepted and recognised process in the Malaysian construction industry.